2021
DOI: 10.31083/j.jin.2021.01.228
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of serum pentraxin 3 for intracerebral hemorrhage mortality

Abstract: Pentraxin 3 is considered an important inflammatory marker is known to increase in patients with ischemic stroke, but the relationship between pentraxin 3 and intracerebral hemorrhage mortality is unclear. The purpose of this study is to investigate the level of pentraxin 3 in serum and its impact on prognosis in 307 patients with intracerebral hemorrhage. During the 5-year follow-up, the mortality rate of patients with intracerebral hemorrhage was 22.5%. The serum pentraxin 3 level of the brain-dead patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In a study including 307 ICH patients, it was shown that pentraxin3 (blood samples were drawn within 24 h after ictus) tends to increase after symptom onset. Additionally, high levels of pentraxin3 in ICH patients were correlated with increased mortality during the 5-year follow-up period [61].…”
Section: Pentraxin 3 (Ptx3)mentioning
confidence: 92%
“…In a study including 307 ICH patients, it was shown that pentraxin3 (blood samples were drawn within 24 h after ictus) tends to increase after symptom onset. Additionally, high levels of pentraxin3 in ICH patients were correlated with increased mortality during the 5-year follow-up period [61].…”
Section: Pentraxin 3 (Ptx3)mentioning
confidence: 92%